Clinical use of a neuronavigation system in hemangioblastoma resection of posterior cranial fossa. Issue 3 (May 2012) - Chen, Weiqiang; Zhang, Guangyu; Lin, Cai; Yang, Yingming; Cai, Danhui; Huang, Mindong; Xu, Yankai; Cai, Chuwei; Li, Wang'an; Lin, Chonghui
Abstract: The aim of this study was to retrospectively evaluate the effectiveness of the Stryker Leibinger neuronavigation system in surgical resection of hemangioblastomas of the posterior fossa. The study included 16 cases of solid hemangioblastoma of posterior cranial fossa treated since we began using Stryker Leibinger neuronavigation system-assisted microneurosurgery in 2003. These cases were compared on the basis of time, blood loss, and complications to 19 similar cases of solid hemangioblastoma that underwent conventional microneurosurgical resection prior to 2003. All patients in the experimental (neuronavigation-assisted) group underwent surgical resection without complications while the control groups' resections all involved blood loss related to the longer operation time. Neuronavigation also resulted in a clear field of surgical vision and clear lesion boundaries, making it easier to remove lesions and reduce accidental injury of adjacent normal structures. The application of navigation technology is very valuable for solid hemangioblastoma operations not only by shortening operative time, thereby significantly reducing operative blood loss, but also by making surgical excision easier, reducing damage to adjacent normal structures, and decreasing surgical complications and mortality.